Roles of tumor-associated macrophages in triple-negative breast cancer progression - Wu, Tianhai; Liao, Yuling (Frontiers in Immunology, 2025)
Triple-negative breast cancer (TNBC) is an aggressive subtype characterized by the absence of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) expression. It is associated with a high risk of recurrence, metastasis, and limited therapeutic options. Tumor-associated macrophages (TAMs) play a central role in TNBC progression by shaping an immunosuppressive tumor microenvironment. Primarily polarized toward an M2-like phenotype under the influence of cytokines such as IL-10 and TGF-β, TAMs facilitate tumor growth, angiogenesis, metastasis, and immune evasion through multiple mechanisms. This review summarizes current understanding of TAM recruitment, polarization, and pro-tumoral functions in TNBC, and outlines emerging therapeutic strategies aimed at depleting TAMs, reprogramming them to an anti-tumor M1-like state, or blocking the CD47-SIRPα phagocytosis checkpoint. These approaches offer promising avenues for reprogramming the TNBC microenvironment and improving clinical outcomes.